Patient Controlled Encryption: Patient Privacy in Electronic Medical Records - Benaloh, Josh; Chase, Melissa; Horvitz, Eric; Lauter, Kristin (The ACM Cloud Computing Security Workshop, 2009)
We explore the challenge of preserving patients’ privacy in electronic health record systems. We argue that security in such systems should be enforced via encryption as well as access control. Furthermore, we argue for approaches that enable patients to generate and store encryption keys, so that the patients’ privacy is protected should the host data center be compromised. The standard argument against such an approach is that encryption would interfere with the functionality of the system. However, we show that we can build an eﬃcient system that allows patients both to share partial access rights with others, and to perform searches over their records. We formalize the requirements of a Patient Controlled Encryption scheme, and give several instantiations, based on existing cryptographic primitives and protocols, each achieving a diﬀerent set of properties.